Boosting photoelectrochemical performance of GaN nanowall network photoanode with bacteriorhodopsin. (1st January 2020) - Devi, Pooja; Thakur, Anupma; Ghosh, Dibyendu; Senthil Prasad, E.; Shivaprasad, S.M.; Sinha, R.K.; Kumar, Praveen
Abstract: The ever-increasing demand for renewable and clean energy sources has prompted the development of novel materials for photoelectrochemical (PEC) water splitting, but efficient solar to hydrogen conversion remains a big challenge. In this work, we report a bio-nanohybrid strategy in a photo-system to simultaneously enhance the charge separation and water splitting efficiency of photoanode (PA) by introducing Bacteriorhodopsin (bR), a natural proton pumping photosystem and GaN nanowall network (NWN), a direct band gap and corrosion-resistant semiconductor. The experimental study reveals that this combination of bR and GaN NWN has huge potential as a light-activated sensitizer as well as proton pumping source to achieve enhance photocurrent density in hydrogen evolution reaction (HER). Consequently, this synergistic effect in bR/GaN NWN PA gives rise to largely enhanced applied bias photon-to-current efficiency (ABPE) 7.8% and photocurrent density (28.74 mA/cm 2 at 1.0 V vs RHE). It is worth mentioning that the photocurrent density of bR/GaN NWN, to the best of our knowledge, is superior to previously reported bR-based PAs and bio-photoelectric devices reported till today for solar-to-hydrogen fuel generation. Graphical abstract: Image 1 Highlights: First report on GaN NWN as photoanode with bR into electrolyte. Measured photocurrent density is 28.74 mA/cm 2 at 1.0 V (vs RHE). Largely enhanced applied bias photon-to-current efficiency (ABPE) 7.8%.